2012
DOI: 10.1673/031.012.5101
|View full text |Cite
|
Sign up to set email alerts
|

Role of Proteases in Extra-Oral Digestion of a Predatory Bug,Andrallus spinidens

Abstract: Roles of salivary proteases in the extra-oral digestion of the predatory bug, Andrallus spinidens Fabricius (Hemiptera: Pentatomidae) were studied by using 2% azocasein as a general substrate and specific protease substrates, as well as synthetic and endogenous inhibitors. It was found that salivary glands of A. spinidens have two anterior, two lateral, and two posterior lobes. Azocasein was used to measure the activity of general proteases in the salivary glands using different buffer solutions. The enzyme ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 35 publications
3
12
0
1
Order By: Relevance
“…Fourth and fifth instars are mostly solitary (Manley 1982). A. spinidens uses extraoral digestion and attacks by inserting stylets into the prey body (Cohen 1998;Zibaee et al 2012). This attack behavior is easy to observe, making the nymphs of A. spinidens well suited for tests on the individual effects of group predation.…”
Section: Introductionmentioning
confidence: 99%
“…Fourth and fifth instars are mostly solitary (Manley 1982). A. spinidens uses extraoral digestion and attacks by inserting stylets into the prey body (Cohen 1998;Zibaee et al 2012). This attack behavior is easy to observe, making the nymphs of A. spinidens well suited for tests on the individual effects of group predation.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the short period of contact of the saliva with the plant food outside the intestinal tract, little digestion occurs before ingestion and normally low levels of digestive enzymes (mainly carbohydrases, such as polygalacturonases and amylases) are found in the saliva compared to the midgut (Agusti and Cohen, ; Walker and Allen, ; Mehrabadi et al., ). This situation is in contrast to what is observed in predaceous bugs, where pre‐oral digestion is normal and high concentrations of digestive enzymes (specially peptidases) can be found in the saliva (Zeng and Cohen, ; Zibaee et al., ).…”
Section: Introductionmentioning
confidence: 61%
“…These biochemical characteristics can sometimes be related to the environmental conditions under which the insect species evolved. For example, the salivary gland proteinases involved in extraoral digestion in Heteroptera exhibit a low temperature optimum (Oliveira et al., ; Zibaee et al., ). Similarly, among‐ and within‐species differences in the efficiency of substrate cleavage and sensitivity to TLCK (Novillo et al., ; Lam et al., ; Oliveira et al., ; Zibaee et al., ) might reflect adaptation to a specific food.…”
Section: Structural Diversity Of Insect Digestive Trypsinsmentioning
confidence: 99%
“…Experiments with omnivores (García et al., ) as well as comparisons between phylogenetically close species with phytozoophagous and zoophytophagous feeding habits reflect the inverse ratio of proteinases and amylase on plant‐ and animal‐based diets. Investigations on representatives of Heteroptera belonging to the same families (Cohen, ; Cohen & Wheeler, ; Agusti & Cohen, ; Zeng & Cohen, ; Zhu et al., ; Swart et al., ; Wright et al., ; Azevedo et al., ; Guedes et al., ; Bigham & Hosseininaveh, ; Zibaee et al., ) have shown that incorporation of animals into a diet led to evolution of the following physiological adaptations: (1) higher protease activity in salivary glands than gut, (2) a decreased amylase‐to‐trypsin ratio, and (3) an increased proportion of trypsin in total protease activity. Strictly phytophagous Miridae lack salivary gland proteinases (Cohen & Wheeler, ), whereas the presence of trypsin and the lack of chymotrypsin, elastase, and amylase are characteristics of a strictly zoophagous feeding habit (Cohen, ).…”
Section: Structural Diversity Of Insect Digestive Trypsinsmentioning
confidence: 99%